2022
DOI: 10.1101/2022.09.07.506878
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunogenicity and Protective Efficacy of a SARS-CoV-2 mRNA Vaccine Encoding Secreted Non-Stabilized Spike Protein in Mice

Abstract: Establishment of an mRNA vaccine platform in low- and middle-income countries (LMICs) is important to enhance vaccine accessibility and ensure future pandemic preparedness. Here, we describe the preclinical studies of a SARS-CoV-2 mRNA encoding prefusion-unstabilized ectodomain spike protein encapsulated in lipid nanoparticles (LNP) "ChulaCov19". In BALB/c mice, ChulaCov19 at 0.2, 1, 10, and 30 μg given 2 doses, 21 days apart, elicited robust neutralizing antibody (NAb) and T cells responses in a dose-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…ChulaCov19 was designed in Thailand and manufactured in North America for early clinical trials, in parallel with large-scale production capacity development in Thailand. In rodent and macaques, ChulaCov19 elicited strong B-and T-cell responses 3 .…”
Section: Pseudovirus Neutralization Tests (Psvnt-50)mentioning
confidence: 99%
“…ChulaCov19 was designed in Thailand and manufactured in North America for early clinical trials, in parallel with large-scale production capacity development in Thailand. In rodent and macaques, ChulaCov19 elicited strong B-and T-cell responses 3 .…”
Section: Pseudovirus Neutralization Tests (Psvnt-50)mentioning
confidence: 99%
“…In contrast, dipeptidyl peptidase (DPP)-4 and aminopeptidase N (APN) receptors of other CoVs are not used by SARS-CoV-2 (Zhou, P et al, 2020). DPP-4 is a particular receptor for MERS-CoV (Prompetchara et al, 2020;Wan et al, 2020) while SARS-CoV-2 and SARS-CoV recognize ACE2. In addition, the spikes, RBDs, and RBM (receptor binding motif) of human MERS-CoV and bat MERS-like Covs have a lower similarity in their sequencing proteins (Wan et al, 2020).…”
Section: A Origin Of Sars-cov-2 and Its Genetic Featuresmentioning
confidence: 99%
“…Additionally, the severity of COVID-19 and patient death associated with those changing levels of the neutrophils and lymphocytes (Prompetchara et al, 2020). Titers of IgG and IgM have recorded an elevated level in the serum of SARS-CoV-2 patients (Zhou,P et al, 2020).…”
Section: Immune Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, cryo-electron microscopy studies showed the overall structures of S with or without the diproline substitutions to be highly similar with an overall root mean square deviation of 0.54( 22 ). In mice, the 2P substitutions were not required for potent immunogenicity of SARS-CoV-2 spike ( 23 ). It should also be noted that the Oxford-AstraZeneca COVID-19 vaccine developers chose to express from an adenoviral vector spike without the 2P substitutions for their vaccine ( 24, 25 ).…”
Section: Introductionmentioning
confidence: 99%